Consolidación del borde urbano en la zona oriental de Santiago de Cali. (2024)
According to the Territorial Planning Plan, the edge is understood to be the strip of rural land, parallel to the urban perimeter, arranged for an ecological corridor, in arder to contain urbanization processes of the city (POT, 2022). The urban edges in cities are a tapie that is of great relevance in city construction, since they are responsible for delimiting the growth of cities.